Sonographic Evaluation of Ectopic Pregnancies - ASGHAR, M (Annals of King Edward Medical University, 2021)
This study was carried out in the Radiology Department, District Head Quarter Teaching Hospital (D.H. Qr) and Dera X-Rays / Ultrasound Clinic. Dera Ismail Khan, NWFP, by performing abdominal and pelvic ultrasonography of all the suspected patients and endo-vaginal of selected cases by comparing with other modalities used for the diagnosis of pregnancy especially the ectopic. Eighty-five percent cases of ectopic pregnancies were diagnosed by abdominal / pelvic ultrasonography, while this ratio was increased up to 95% by endo-vaginal ultrasonography in those cases where the abdominal sonography was not helpful for accurate diagnosis. The study concluded that increased availability of ultrasonography leads to improve quality in the detection of ectopic pregnancy. It is necessary to screen all the patients with first trimester cramping and bleeding by ultrasonography.